PENGARUH MODEL PEMBELAJARAN JIGSAW PADA MATERI HIDROKARBON KELAS XI MIPA (SMA N 1 Cerenti) - Ramadanil Putri Yanti; Asregi Asril; Dwi Putri Musdansi (Universitas Islam Kuantan Singingi, 2020)
This study aims to determine student learning outcomes in Hydrocarbons material in class XI MIPA SMA Negeri 1 Cerenti. This research as a quantitative research type of quasi-experimental designwith posttets-only control design experimental design. The sample in this study were students of class XI MIPA 4 as an experimental class and class XI MIPA 1 as a control class. The sampling technique was cluster random sampling. This study used the Kolmogorov-Smirnov test. In this study usung the “t” test that is independent sample t-test. Based on the results o the final hypothesis test which was analyzed using thee independent sample test, the significance value (2-tailed) was obtained is 0,000<0,05. Because thi study uses 1-tailed, the significance value is 2-tailed = 0,000<0,05 so that H0 is rejected. The final test results obtained Sig (1-tailed) is 0,000 < 0,05 which mean H0 was rejected. It can be concluded that the learning outcomes of chemistry using the Jigsaw learning model was better which do conventional learning.